Seleccion de progenitores y planificacion de cruzamientos - Masaya S, P (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Criteria to select parents within a breeding program involving local or introduced var. are given. Every yr. the CIAT Bean Program publishes the results of international trials, highlighting the importance of desirable crop characteristics for each national program. Parental selection can be directed toward the improvement of var. or of one character, e.g., disease resistance. Since in some cases complete resistance is not obtained, tolerant parents can be combined to produce cumulative tolerance. The environment is also important, inducing variations in photoperiod, precipitation, temp., and even in disease pathogenicity (strains); this affects complex polygenetically-controlled characters, such as yield. (CIAT)